Association between remnant cholesterol and chronic kidney disease in Chinese hypertensive patients - Yuan, Ting; Ding, Congcong; Xie, Yanyou; Zhou, Xinlei; Xie, Chong; Wang, Tao; Yu, Chao; Zhou, Wei; Zhu, Lingjuan; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2023)
Abstract Background: Remnant cholesterol (RC) and chronic kidney disease (CKD) have not been definitively linked in individuals with different characteristics. We aimed to investigate the relationship between serum RC level and CKD and examine possible effect modifiers in Chinese patients with hypertension. Methods: Our study was based on the Chinese H-type Hypertension Project, which is an observational registry study conducted in real world settings. The outcome was CKD, defined as an estimated glomerular filtration rate of less than 60 ml/min·1.73 m2. Multivariate logistic regression and smooth curve fitting were used to analyze the association between RC and CKD. Subgroup analyses were subsequently conducted to examine the effects of other variables. Results: The mean age of the 13,024 patients with hypertension at baseline was 63.8±9.4 years and 46.8% were males. A conspicuous linear positive association was observed between RC level and CKD (per SD increment; odds ratio [OR], 1.15; 95% confidence interval [CI], 1.08–1.23). Compared with the lowest quartile group of RC, the risk of CKD was 53% higher (OR, 1.53; 95% CI, 1.26–1.86) in the highest quartile group. Furthermore, a stronger positive association between RC level and CKD was found among participants with higher body mass index (BMI, <24 vs. ≥24 kg/m2; P-interaction = 0.034), or current non-smoker (smoker vs. non-smoker; P-interaction = 0.024). Conclusions: Among Chinese adults with hypertension, RC level was positively associated with CKD, particularly in those with a BMI≥24 kg/m2 and current non-smokers. These findings may help improve lipid management regimens in patients with hypertension